Targeting cancer: designing drugs against Hsp90 - Chiosis, Gabriela (Henry Stewart Talks, 2007)
Heat shock protein 90 (Hsp90), a target in cancer, Discovery of the first known Hsp90 inhibitor, geldanamycin, Use of geldanamycin to understand the role of Hsp90 in malignant transformation, Discovery of novel Hsp90 inhibitors, Development and applications of Hsp90 inhibitors